The Knowledge, Attitude, and Practice of the Adoption of Green Fashion Innovation - Alaeddin Ahmad; Yasmeen Madi; Mohammad Abuhashesh; Nawras M. Nusairat; Ra’ed Masa’deh (Journal of Open Innovation: Technology, Market and Complexity, 2020)
Environmental pollution from garment manufacturing is a major concern due to its widely-felt impact on climate change. Consequently, the researchers set about assessing KAP (Knowledge, Attitude and Practice) and its relationship with, and impact on, green fashion innovation adoption among Jordanian companies. This work examined the relationship between the independent variables, represented by KAP, and the dependent variable, which was Green Fashion Innovation Adoption in Jordan. A quantitative approach utilized a cross-sectional survey to gather primary data from upper and middle-level management in Jordanian garment companies. The sample size was 257 valid questionnaires. The results showed a statistically significant impact of knowledge and attitude toward green fashion innovation adoption, but failed to identify a statistically significant impact of practice on the same. This research contributes positively to the diffusion of awareness about going green in innovative methods and systems in Jordan’s garment industry, and provides suggestions to practitioners.